Author Chris Crutcher: Speaking Out on Teachers’ Role in Aiding Children of Trauma - Lori Goodson (Educational Considerations, 2019)
Nationally known young adult author Chris Crutcher shares his thoughts on how teachers can help students who are dealing with trauma in their lives.
Keywords: Teachers; trauma; children; teacher training; support